[latex] \frac{ \sqrt{5} - \sqrt{3} }{ \sqrt{5+ \sqrt{3} } } - \frac{ \sqrt{5} + \sqrt{3} }{ \sqrt{5}- \sqrt{3} } [/latex] упростить выражение

[latex] \frac{ \sqrt{5} - \sqrt{3} }{ \sqrt{5+ \sqrt{3} } } - \frac{ \sqrt{5} + \sqrt{3} }{ \sqrt{5}- \sqrt{3} } [/latex] упростить выражение
Гость
Ответ(ы) на вопрос:
Гость
=[latex] \frac{( \sqrt{5} - \sqrt{3} )^2-( \sqrt{5}+ \sqrt{3} )^2}{( \sqrt{5)^2} -( \sqrt{3} )^2} = \frac{5+3-2 \sqrt{15} -5-3-2 \sqrt{15} }{5-3} = \frac{-4 \sqrt{15} }{2} =-2 \sqrt{15} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы